Error-resilient coding in JPEG-2000 and MPEG-4 - Moccagatta, I.; Soudagar, S.; Liang, J.; Chen, H. (IEEE journal on selected areas in communications, 2000)
The rapid growth of mobile communications and the widespread access to information via the Internet have resulted in a strong demand for robust transmission of compressed image and video data for various multimedia applications and services. The challenge of robust transmission is to protect the compressed image/video data against hostile channel conditions while bringing little impact on bandwidth efficiency. This paper addresses this critical problem and provides an overview of the error-resilient approaches that have been evaluated and inserted into the emerging JPEG-2000 wavelet-based image coding standard. We also review the state-of-the-art techniques adopted in the MPEG-4 standard for robust transmission of video and still texture data. These techniques include resynchronization strategies, data partitioning, reversible VLCs, and header extension codes. The performance of these approaches under various channel conditions is evaluated.